The impact of the World War I on the law governing the treatment of prisoners of war and the making of a humanitarian subject - Wylie, Neville; Cameron, Lindsey (Oxford University Press, 2018)
This paper evaluates the impact of the First World War on the development of international humanitarian law (IHL) regarding the treatment of prisoner of war (POW). In contrast to traditional scholarship, which overlooks the war’s significance on the jus in bello, we argue that in the area of POW law, the changes brought about by the war were significant and long lasting, and led to the creation of a POW convention in 1929 that set IHL onto a markedly different path from that followed before 1914. Although the process was only completed with the signing of the four Geneva Conventions in 1949, many of the distinguishing features of modern POW law had their roots in the experience of captivity during the First World War and the legal developments that followed in its wake. In particular, the scale, duration and intensity of wartime captivity after 1914 gave rise to a conceptual shift in the way POWs were perceived, transforming their status from ‘disarmed combatants’, whose special privileges were derived from their position as members of the armed forces, to ‘humanitarian subjects’, whose treatment was based on an understanding of their humanitarian needs and rights.